Governing the Local? A Response to Kevin Stenson - John Clarke (Social Work & Society, 2008)
Kevin Stenson's article offers a powerful argument for examining governmentality in particular local configurations rather than as relatively abstract and text-centred studies of changing mentalities and rationalities of rule. I think this is an important endeavour, partly because more situated analyses of governmentality are necessary to enrich the analytical (and political) significance of the perspective; and partly because the view from governmentality has a capacity to enrich our understandings of governance, policy and practice. Kevin's own discussion of community safety in the Thames Valley area demonstrates just how much such a situated analysis might add to an understanding of liberal rule in England in the 21st century.